Implementation of Authentic Assessment in PAI Learning in Improving Student Motivation and Learning Achievement at SDIT Semarak Rejang Lebong - Putri Adelia; Rejabil Anbia; Deri Wanto; Mirzon Daheri (Indonesian Journal for Islamic Studies, 2024)
The aim of this research is to evaluate the impact of using authentic assessment on the motivation and learning achievement of students at SD IT Semarak Rejang Lebong, especially in learning Islamic Religious Education (PAI). This research applies a descriptive and qualitative approach with a focus on SD IT Semarak Rejang Lebong. In line with John Creswell's definition of qualitative research, this methodology involves open data collection, analysis of text or images, representation of information through figures and tables, and personal interpretation of findings. The implementation of authentic assessment in PAI learning at SDIT Semarak Rejang Lebong is believed to be able to improve learning outcomes and student creativity. In this context, authentic assessment is considered very effective because it encourages students to demonstrate their individual abilities. Although some students may have unsatisfactory learning results, the majority of them overall get good grades. If there are students who have not reached Minimum Competency (KKM), the teacher takes remedial steps to provide additional assistance and improve student understanding. Overall, this research highlights that the implementation of authentic assessment in PAI learning at SD IT Semarak Rejang Lebong has a positive impact on students' motivation and learning achievement, namely with remedial steps taken to support their development.